Screening of Dystrophin Gene Deletions in Egyptian Patients with DMD/BMD Muscular Dystrophies. Issue 3 (2000) - Effat, Laila K.; El-Harouni, Ashraf A.; Amr, Khalda S.; El-Minisi, Tarik I.; Abdel Meguid, Nagwa; El-Awady, Mostafa
Abstract : Duchenne muscular dystrophy (DMD) and Becker muscular dystrophy (BMD) are allelic disorders caused by mutations within the dystrophin gene. Our study has identified 100 Egyptian families collected from the Human Genetics Clinic, National Research Center, Cairo. All cases were subjected to complete clinical evaluation pedigree analysis, electromyography studies, estimation of serum creatine phosphokinase enzyme (CPK) levels and DNA analysis. Multiplex PCR using 18 pairs of specific primers were used for screening of deletion mutations within the dystrophin gene. A frequency of 55% among the families. Sixty per cent of detected deletions involved multiple exons spanning the major or the minor hot spot of the dystrophin gene. The remainder 40% which mainly involved exon 45. Comparing these findings with frequencies of other countries it was found that our figures fall within the reported range of 40%– for deletions. The distribution of deletions in our study and other different studies was variable and specific ethnic differences do not apparently account for specific deletions. In addition this study concluded that employment of the 18 exon analysis is a cost effective and a highly accurate (97% to launch a nationwide program.